2018
DOI: 10.1007/s13364-018-0357-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro study of caecal microbial activity in brown hares and domestic rabbits which were offered the same diet

Abstract: The products of the microbial activity in the large intestine are an important source of energy for herbivores. A previous study showed differences in caecal methanogenesis and short-chain fatty acid (SCFA) profiles between brown hares and domestic rabbits. The present study was performed on animals which were offered the same diet to eliminate the impact of diet on the comparative analyses of microbial metabolites. Caecal samples of hares and rabbits were incubated in triplicate, i.e. without any supplementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This phylum is dominated by bacteria from the genus Akkermansia , which are noted to be positively influenced by dietary polyphenols ( Roopchand et al, 2015 ; Anhê et al, 2016 ). Polyphenols are metabolised by intestinal bacteria to generate short-chain fatty acids (SCFAs), and previous studies have demonstrated that rabbits produce a higher concentration of SCFAs than hares, with a higher ratio of butyrate to propionate ( Miśta et al, 2015 ; Marounek, Brezina & Baran, 2000 ; Miśta et al, 2018 ). Again, it is unknown whether the Akkermansia detected in rabbits in this study permit the digestion of these polyphenols, influencing the dietary preference of rabbits, or whether the intake of polyphenols supports a detectable Akkermansia population in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…This phylum is dominated by bacteria from the genus Akkermansia , which are noted to be positively influenced by dietary polyphenols ( Roopchand et al, 2015 ; Anhê et al, 2016 ). Polyphenols are metabolised by intestinal bacteria to generate short-chain fatty acids (SCFAs), and previous studies have demonstrated that rabbits produce a higher concentration of SCFAs than hares, with a higher ratio of butyrate to propionate ( Miśta et al, 2015 ; Marounek, Brezina & Baran, 2000 ; Miśta et al, 2018 ). Again, it is unknown whether the Akkermansia detected in rabbits in this study permit the digestion of these polyphenols, influencing the dietary preference of rabbits, or whether the intake of polyphenols supports a detectable Akkermansia population in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…This phylum is dominated by bacteria from the genus Akkermansia, which are noted to be positively influenced by dietary polyphenols (54,55). Polyphenols are metabolised by intestinal bacteria to generate short-chain fatty acids (SCFAs), and previous studies have demonstrated that rabbits produce a higher concentration of SCFAs than hares, with a higher ratio of butyrate to propionate (56)(57)(58). Again, it is unknown whether the Akkermansia detected in rabbits in this study permit the digestion of these polyphenols, influencing the dietary preference of rabbits, or whether the intake of polyphenols supports a detectable Akkermansia population in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hares have a higher gastrointestinal passage rate compared to rabbits, while rabbits retain digesta longer in order to maximise the efficiency of nutrient extraction (53). Rabbits also have a greater ability to digest hemicelluloses and have a higher rate of methanogenesis compared to hares (56)(57)(58)61).…”
Section: Discussionmentioning
confidence: 99%